2007
DOI: 10.2466/pms.104.4.1289-1296
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Effect of Three Yoga Breathing Techniques on Performance on a Letter-Cancellation Task

Abstract: The effects of three yoga breathing practices were evaluated on performance on a letter-cancellation task which is a left-hemisphere dominant task. The three yoga breathing practices (right, left, and alternate nostril breathing) were selected because unilateral forced nostril breathing stimulates the contralateral hemisphere. There were 20 male volunteers whose ages ranged from 20 to 45 years (M age=28.4 yr., SD=5.7). All subjects were assessed before and after four sessions, i.e., right nostril yoga breathin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 17 publications
1
37
1
Order By: Relevance
“…[7][8][9][10][11][12][13] Eleven studies included subjects who were practitioners of breathing exercises and other components of yoga. [14][15][16][17][18][19][20][21][22][23][24] Their experience ranged from seven days to eighty-six months. Twenty-six studies did not provide details regarding prior yoga experience.…”
Section: Participants Characteristicsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Eleven studies included subjects who were practitioners of breathing exercises and other components of yoga. [14][15][16][17][18][19][20][21][22][23][24] Their experience ranged from seven days to eighty-six months. Twenty-six studies did not provide details regarding prior yoga experience.…”
Section: Participants Characteristicsmentioning
confidence: 99%
“…The reason for selection of the techniques was that they were effective in addressing the nervous system as addressed in the literature (Telles, et al, 2007), with no side-effects and easy to administer with young children. In the first breathing technique, the participant breathes in and out of the nose deeply.…”
Section: Intervention Frameworkmentioning
confidence: 99%
“…The two breathing techniques of deep breathing and alternate nostril breathing purport to provide therapeutic benefits for memory and brain cells (Telles, et al 2007). Deep breathing exercise stimulates slow, deep, and rhythmic breathing, which results in increasing the amount of oxygen in the blood stream, thereby improving blood circulation.…”
Section: Therapeutic Breathing Techniques and The Achievement Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…Sahasi et al (1989) has demonstrated the effectiveness of yogic techniques in the management of anxiety and reported increased attention and concentration [7]. The studies on different yogic techniques, i.e., deep relaxation technique (DRT) and supine rest (SR) [8], pranayama [9] demonstrated an increase in attention. Two yoga-based relaxation techniques, namely, cyclic meditation (CM) and supine rest (SR) on the six letter cancellation task (SLCT) reported significant increase attention scores in school students [10].…”
Section: Introductionmentioning
confidence: 99%